Pengaruh Kesadaran Masyarakat dan Pengetahuan Pajak Terhadap Kepatuhan Dalam Membayar Pajak Bumi dan Bangunan di Desa Manjalling Kabupaten Bulukumba - Irfansyah, Muh. Nur; Marlinah, Andi; Nianty, Dara Ayu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the influence of public awareness and tax knowledge on compliance in paying land and building taxes in Manjalling Village, Bulukumba Regency. Using a quantitative approach, primary data were collected from a sample of 100 residents through purposive sampling. The study reveals that both public awareness and tax knowledge partially have a positive and significant effect on tax compliance. Simultaneously, these variables also demonstrate a positive and significant influence on compliance behavior. The findings suggest that improving both awareness and understanding of tax obligations can enhance community compliance in land and building tax payments. This study contributes to better policy design and education strategies for improving local tax compliance.